Service Life of Railway Wood Sleepers in Indonesia - Djarwanto Djarwanto; Sihati Suprapti; Sri Rulliaty (Wood Research Journal, 2015)
Wood offers natural advantages tremendously such as their elasticity, flexibility and resistance against compression as well as force impact.  Therefore, wood material is astonishingly better material than concrete for railway sleepers. In spite of wood material’s advantages, the material is susceptible to attack by organisms. This paper observes the service life of wood sleepers in Java, Indonesia. Wood sleepers were observed visually from the ground railway system, Banten Province includes wood species identification macroscopically and organism’s attack. Results reveal that natural wood resistance of the sleepers are relatively high, then sleepers were predicted to be last long. Sleepers wood species are teak (Tectona grandis), balau (Hopea sp.), merbau (Intsia bijuga), and ulin (Eusideroxylon zwageri). Sleepers were also found deteriorated by fungus during five months instalment. Decaying fungi observed are Dacryopinax sp., D. spathularia, Lentinus sp., Panus sp., Pycnoporus sp., P. sanguineus, Polyporus spp., Schizophyllum commune, and Trametes sp.